ВЗАИМОДЕЙСТВИЕ СЛЕДОВАТЕЛЯ С ЭКСПЕРТАМИ ПРИ ПРОФИЛАКТИКЕ ДТП НА ПРИМЕРЕ УКРАИНЫ - Чичиркин, Андрей Александрович (SUPREMANCE OF LAW, 2018)
The article focuses on such an important condition for increasing the effectiveness of preventive activities of expert criminalistic units as close interaction with the investigative apparatus of law enforcement agencies. The ways of improving the legislative support for the prevention of crime in general, and in the commission of accidents in particular, for example, the adoption of the general law of Ukraine «On the Prevention ofCrime», which should provide for specific measures to prevent offenses in the field of accidents.